NEUMONÍA POR PNEUMOCYSTIS JIROVECII EN PACIENTE ADOLESCENTE INMUNOSUPRIMIDO NO VIH POSITIVO: UN REPORTE DE CASO - Sebastian Hernández (Asociación Colombiana de Infectología, 2021)
The pneumonia in the immunocompromised patient is a diagnostic challenge that the clinician faces more and more frequently, every time we talk about ground glass infiltrates it is necessary to always take into account the possibility of pneumonia due to Neumocystis Jirovecii, which for a long time was thought as a disease of the immunosuppressed host with HIV, but that across the time it has manifested itself in patients with solid organ transplants and hematopoietic precursors, associated with autoimmunity, the chronic use of corticosteroids and more recently the use of biological therapy. The description of this disease and the diagnostic methods in non-HIV immunosuppressed hosts is not entirely clear, we know that the treatment of choice in these cases is trimethropin-sulfamethoxazole (TMP-SMX), which does not have high-quality evidence at the time of a dose or a time of established duration. We present the case of a patient diagnosed with glomerulonephritis due to corticodependent minimal change disease and who suffers from pneumocystis Jirovecii pneumonia confirmed by histopathology, which received treatment and had a positive outcome